1983
DOI: 10.1002/pol.1983.170211014
|View full text |Cite
|
Sign up to set email alerts
|

Structure and sorption properties of the polyion complex between poly(acrylic acid) and poly(4‐vinylpyridine)

Abstract: A polyion complex was formed from poly(acrylic acid) (PAA) and poly(4‐vinylpyridine) (PVP). Its structure and composition were examined by means of infrared spectroscopy (IR), x‐ray photoelectron spectroscopy (XPS), and elemental analysis. The polyion complex was obtained by dissolving PAA and PVP together in methanol. The composition of the polyion complex was independent of stirring speed, mixing sequence, and standing time after mixing. However, the composition depended on the concentrations and the ratio o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…is 0.49 for the P4VP-ethanol system 13 and V 1 is 58.3 g cm Ϫ3 for ethanol. The M c values, thus determined from eq.…”
Section: Determination Of M C Values Of Gelsmentioning
confidence: 99%
“…is 0.49 for the P4VP-ethanol system 13 and V 1 is 58.3 g cm Ϫ3 for ethanol. The M c values, thus determined from eq.…”
Section: Determination Of M C Values Of Gelsmentioning
confidence: 99%
“…While polystyrene is immiscible with poly(ethylene oxide) or poly(propylene oxide), polystyrene ionomers containing 5 -10 mol-% lithium methacrylate show considerable miscibility with the two polar polymers 6) . Poly(4-vinylpyridine) (P4VPy), a proton-accepting polymer, is miscible with a large number of proton-donating polymers such as poly(p-vinylphenol) (PVPh) 7,8) , poly(acrylic acid) (PAA) 9) , poly(methacrylic acid) (PMAA) 9,10) , poly(monoalkyl itaconate)s [11][12][13][14][15] and poly[2-acrylamido-2-methylpropanesulfonic acid] 16,17) . Blends of P4VPy or pyridine-containing polymers and ionomers have also been studied [18][19][20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…The hydrogen bonding between PAA and P4VP (or P2VP) was also reported by several authors [20,21]. It can be suggested that in PAA/PS-b-P4VP complexes, hydrogen bonding interaction also exists between pyridine groups and acrylic acid groups.…”
Section: Resultsmentioning
confidence: 66%